Chapter Advances on coastal erosion assessment from satellite earth observations: exploring the use of Sentinel products along with very high resolution sensors - Jones, Martin (Proceedings e report, 2020)
This work proposes the use of automatic co-registered satellite images to obtain large, high frequency and highly accurate shorelines time series. High resolution images are used to co-register Landsat and Sentinel-2 images. 90% of the co-registered images presented vertical and horizontal shift lower than 3 m. Satellite derived shorelines presented errors lower than mission's precision. A discussion is presented on the applicability of those shorelines through an application to Tordera Delta (Spain).